2021
DOI: 10.1073/pnas.2109432118
|View full text |Cite
|
Sign up to set email alerts
|

LRRC8A reduces intracellular chloride to permit WNK activation in response to hypertonic stress

Abstract: See companion article, "LRRC8A-containing chloride channel is crucial for cell volume recovery and survival under hypertonic conditions," 10.1073/ pnas.2025013118.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Osmotic activation accomplished by hyperosmotic pipette solution, as used in our experiments and in classical VRAC studies [51], is consistent with the activation of lysine deficient protein kinases (WNKs), ancient cytoplasmic regulatory scaffolds sensitive to low [Cl − ] and hyperosmotic cytoplasmic conditions [52]. For WNKs to be able to orchestrate regulatory volume increase in mammalian cells, there is an absolute requirement for functional VRAC to be present [53].…”
Section: Discussionsupporting
confidence: 69%
“…Osmotic activation accomplished by hyperosmotic pipette solution, as used in our experiments and in classical VRAC studies [51], is consistent with the activation of lysine deficient protein kinases (WNKs), ancient cytoplasmic regulatory scaffolds sensitive to low [Cl − ] and hyperosmotic cytoplasmic conditions [52]. For WNKs to be able to orchestrate regulatory volume increase in mammalian cells, there is an absolute requirement for functional VRAC to be present [53].…”
Section: Discussionsupporting
confidence: 69%
“…Th activity center of WNKs contains many water molecules. Osmotic pressure by extracting water from the protein shifts the equilibrium to the latter state (Figure 12A) (43)(44)(45). During the revision of the manuscript, a paper reported that hypertonicity induces molecular crowding and phase separation on WNK1 leading to activation of WNK1-OSR1/SPAK pathway (46).…”
Section: Discussionmentioning
confidence: 99%
“…The intracellular Cl – concentration rises initially during cell shrinkage and subsequently from NKCC1-mediated Cl – entry during RVI ( 45 ). How do cells balance the two opposing forces on WNK kinase activity, i.e., inhibition by the high intracellular Cl – concentration and activation by dehydration?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…WNK1 is known to be activated under hypertonic stress (51,52), and also under hypotonic stress (53,54). All these data are mostly retrieved in short-term osmotic stress experiments (minutes), whereas our osmotic stress assays were done for longer times (days).…”
Section: Inactivation Of Wnk1 Leads To Microtubule Stabilization Modi...mentioning
confidence: 99%